2011
DOI: 10.4236/jct.2011.23039
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Tumor Effect of Cisplatin When Combined with an Anti-Src Kinase Integrin-Based Peptide

Abstract: Background: It is known that active Src kinase promotes survival of ovarian cancer cell lines and inhibition of c-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…6 c). Given that SFK members share a common domain structure 68 and that RSKAKNPLYR has previously been reported to inhibit c-Src activity 53 we next sought to compare the effects of IK14004, RSKAKNPLYR (IK14000) and the dodecanoic acid moiety (IK00041) on the activity of c-Src using a non-cell-based kinase profiling approach. A combination of peptide plus dodecanoic acid, i.e., IK14004, was the most effective inhibitor of c-Src activity at concentrations below 3 µM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 c). Given that SFK members share a common domain structure 68 and that RSKAKNPLYR has previously been reported to inhibit c-Src activity 53 we next sought to compare the effects of IK14004, RSKAKNPLYR (IK14000) and the dodecanoic acid moiety (IK00041) on the activity of c-Src using a non-cell-based kinase profiling approach. A combination of peptide plus dodecanoic acid, i.e., IK14004, was the most effective inhibitor of c-Src activity at concentrations below 3 µM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, targeting calcineurin-dependent NFAT signalling pathways and JAK/STATs have become attractive options against autoimmune diseases 51 , 52 . We have previously reported that an ERK-binding peptide, RSKAKNPLYR, inhibits c-Src activity 53 . Linkages between a peptide drug and a branched lipid unit are thought to enhance drug stability and generate a membrane-like structure with increased lipophilicity 54 .…”
Section: Introductionmentioning
confidence: 99%
“…
Background:The NPxY motif common to all β integrin cytoplasmic domains forms part of a canonical recognition sequence for phosphotyrosine-binding domains which are protein modules present in a wide variety of signaling and cytoskeletal proteins. We have recently reported that a non-naturally occurring peptide, RSKAKNPLYR, derived from the β6 integrin cytoplasmic domain inhibits cancer cell growth in vitro and proposed that this may be due, at least in part, to the inhibition of c-Src activity [1]. In the present study we examined the role of the NPLY motif within RSKAKNPLYR in terms of its requirement for inhibition of cancer cell growth.
…”
mentioning
confidence: 94%
“…We have previously reported that a sequence of 15 amino acids, RSK-AKWQTGTNPLYR, located within the cytoplasmic tail of the β6 integrin subunit binds to extracellular signal-regulated kinase 2 (ERK2) and proposed that this contributes to tumor growth [5]. More recently, we reported that a novel peptide, RSKAKNPLYR, derived from the β6 binding sequence inhibits cancer cell growth in vitro and proposed that this may be due, in part at least, to the inhibition of c-Src activity [1].…”
Section: Introductionmentioning
confidence: 99%